Sacral Emphysematous Osteomyelitis Caused by Escherichia coli after Arthroscopy of the Knee - Mirko Velickovic; Thomas Hockertz (Case Reports in Orthopedics)
Emphysematous osteomyelitis is a rare but serious condition which is often associated with a fatal outcome. The typical appearances of emphysematous osteomyelitis are clusters of small gas bubbles within the medullary cavity. We report a case of a 62-year-old male who presented with emphysematous osteomyelitis due to hematogenous spread of Escherichia coli from the knee after arthroscopy.